2018
DOI: 10.1039/c7ta10632g
|View full text |Cite
|
Sign up to set email alerts
|

Porous CuO microsphere architectures as high-performance cathode materials for aluminum-ion batteries

Abstract: Cathode materials with a porous structure are important in the development of aluminum-ion batteries (AIBs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(68 citation statements)
references
References 40 publications
0
67
1
Order By: Relevance
“…These results demonstrated the potential of RABs for practical applications. To improve the performance of RABs, several kinds of cathode, including modified graphites,10–12 graphene nanosheets,13–15 carbon‐based materials,16–18 transition metal oxides,19–21 and metal sulfides,22–25 have been developed. However, the IL electrolyte has received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated the potential of RABs for practical applications. To improve the performance of RABs, several kinds of cathode, including modified graphites,10–12 graphene nanosheets,13–15 carbon‐based materials,16–18 transition metal oxides,19–21 and metal sulfides,22–25 have been developed. However, the IL electrolyte has received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…All kinds of carbon materials exhibit a reversible capacity of 60–130 mA h g −1 and unparalleled cycle stability. Transition metal oxides, sulfides and selenides have been reported mainly including Co 3 O 4 , CuO, TiO 2 , SnO 2 , Co 3 S 4 , Co 9 S 8 , CuS, FeS 2 , MoS 2 , Mo 6 S 8 , Ni 3 S 2 , NiCo 2 S 4 , SnS 2 , TiS 2 , VS 2 , Cu 2−x Se and CoSe . These materials could provide a higher capacity, but the cycle stability is inferior than carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Regarding the more promising rechargeable AIBs, previous studies demonstrated that the intrinsic hydrogenation over the Al anode and passive oxide layer formation in the aqueous system drastically reduced the battery voltage and efficiency, which lead to the sluggish development of rechargeable aqueous AIBs. [21][22] After then, AIBs have been attracting everincreasing attention in recent years. [20] However, the high operation temperature, electrode solubility, and Al dendrite hinder the practical application of such non-aqueous rechargeable AIBs.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Till the 2010s, the mixture of M + X À and AlCl 3 ionic liquid (IL) electrolyte (where M + could be organic cations, such as imidazolium and pyrrolidinium, and X À represents Cl À , Br À , or I À ) was evidenced to act as efficient media for Al deposition and exfoliation at room temperature. [21][22] After then, AIBs have been attracting everincreasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%